Dermatological Findings in Glaucoma Patients: Comparison Between Pseudoexfoliative and Primary Open-angle Glaucoma - Farnaz Ahmadpour; Yalda Nahidi; Ramin Daneshvar (Journal of Ophthalmic & Vision Research)
Abstract Purpose: To compare the frequency of dermatological manifestations between patients with pseudoexfoliative glaucoma and those with primary open-angle glaucoma. Methods: A cross-sectional study was done on all consecutive pseudoexfoliative glaucoma (PEXG) and primary open-angle glaucoma (POAG) patients evaluated in a tertiary eye hospital during the study period. Eligible patients were referred to the dermatology department for complete skin, hair, nail, and mucosal examinations. Results: Twenty-one patients in the PEXG group and 26 patients in the POAG group were included in this study. The most common skin manifestations in the study were seborrheic dermatitis, dry skin, and cherry angioma. The frequency of lentigines was significantly higher in the PEXG patients than in the POAG group (P = 0.013). More than half of the study population had seborrheic dermatitis (57.1% and 61.5% in the PEXG and POAG groups, respectively); however, the difference between the groups was not statistically significant (P = 0.775). Similarly, the frequencies of skin dryness, cherry angioma, nevus, psoriasis, contact dermatitis, itching, seborrheic keratoses, notalgia paresthetica, and vitiligo in the two groups were not statistically significantly different (P > 0.1 for all comparisons). There was no significant association between the frequency of the investigated skin manifestations and patients' age, visual acuity, intraocular pressure, and cup-to-disc ratio. Conclusion: Integumentary system disorders are pervasive in glaucoma patients, and dermatologic evaluation in glaucoma patients should be considered for diagnostic and therapeutic purposes.